Paleomagnetism and time-stratigraphic correlation of Proterozoic redbeds of the Labrador Trough and outliers of northern Quebec - Schwarz, E. J.; Freda, G. N. (Canadian Journal of Earth Sciences, 1983)
One hundred and forty-two oriented cores were collected from redbeds of the Sakami Formation near LG-4 (85), Dieter (19), Cambrian (18), and Snow-ball (4) lakes, all in Quebec, and from two outliers in Labrador: Evening Lake (6) and Sims Lake (10). A further 73 oriented drill cores were collected from the strongly folded Chakonipau Formation redbeds (44) in the Labrador Trough and undeformed redbeds near Lac Imbault (29) on the western edge of the trough. Thermal demagnetization of the trough redbeds yielded 52 core directions, each of which showed good specimen end points and sufficient homogeneity of magnetization, and 101 such core directions were obtained for the outlier redbeds. In most of these samples, there are no indications that the stable remanence is multi-component, and the fold test yields (for LG-4 Sakami Formation and the Chakonipau Formation) a significant (95% probability) improvement of the dispersion parameter K. Thus, the Chakonipau Formation remanence is probably pre-Hudsonian and the Sakami Formation remanence is probably pre-faulting (not dated). Furthermore, a near reversal (165°) in the Chakonipau Formation suggests that the stable remanence was acquired during or soon after deposition. The pole positions for Circum-Superior orogen rocks, the Proterozoic outliers, and the Sutton Lake inlier suggest: (1) a time-stratigraphic correlation between the LG-4 Sakami, Dieter Lake, Sutton Lake, and the upper part of the Belcher Island sequences; and (2) a time-stratigraphic correlation between the lower part of the Belcher Islands sequence and the Richmond Gulf sequence, which must be substantially older than group 1. The Circum-Superior apparent polar wander path (APWP) is drawn through magnetic North poles from the group 1 poles to the group 2 poles, yielding a slightly lower age for the trough sediments represented by the Chakonipau Formation (two opposing polarities) and the Lac Imbault redbeds. The general North American APWP is simplified by the deletion of the Richmond Gulf South poles, ...